Racism and football - Bradbury, S. (2002)
The article deals with the following topics: 1. Institutionalised Racism 2. Overt crowd racism 3. The role of extreme right wing groups 4. Official concern and the response of government 5. The 'Anti-Nazi' backlash ('Football fans against racism') 6. Racism and football on the continent 7. The CRE/PFA/Football Trust Campaign ("Let's Kick Racism Out of Football") 8. Racism and football: a new direction?